2023
DOI: 10.1186/s13287-023-03380-x
|View full text |Cite
|
Sign up to set email alerts
|

Adipose tissue-derived human mesenchymal stromal cells can better suppress complement lysis, engraft and inhibit acute graft-versus-host disease in mice

Abstract: Background Acute graft-versus-host disease (aGvHD) is a life-threatening complication of allogeneic hematopoietic stem cell transplantation (HSCT). Transplantation of immunosuppressive human mesenchymal stromal cells (hMSCs) can protect against aGvHD post-HSCT; however, their efficacy is limited by poor engraftment and survival. Moreover, infused MSCs can be damaged by activated complement, yet strategies to minimise complement injury of hMSCs and improve their survival are limited. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…Mesenchymal stem/stromal cells (MSCs) are multipotent cells that can be obtained from various tissues (including bone marrow [BM], adipose tissue [AT], umbilical cord, and placenta) [ 29 – 31 ], and apart from regenerative capacities, they harbor immunomodulatory and growth-promoting characteristics [ 32 35 ]. Experimental [ 36 , 37 ] and clinical [ 38 41 ] studies have demonstrated their effectiveness in the treatment of GVHD, and their low and no expression of human leukocyte antigens (HLA) class I and class II, respectively, make them ideal targets for allogeneic transplantation [ 42 ]. Compared to other sources, AT-derived MSCs (AT-MSCs) are easy to obtain [ 43 ], have less genomic instability and senescence than BM-derived MSCs [ 44 ], harbor higher proliferation capacities [ 37 , 45 ], and are superior in inducing anti-inflammatory effects and surviving after transplantation [ 37 , 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mesenchymal stem/stromal cells (MSCs) are multipotent cells that can be obtained from various tissues (including bone marrow [BM], adipose tissue [AT], umbilical cord, and placenta) [ 29 – 31 ], and apart from regenerative capacities, they harbor immunomodulatory and growth-promoting characteristics [ 32 35 ]. Experimental [ 36 , 37 ] and clinical [ 38 41 ] studies have demonstrated their effectiveness in the treatment of GVHD, and their low and no expression of human leukocyte antigens (HLA) class I and class II, respectively, make them ideal targets for allogeneic transplantation [ 42 ]. Compared to other sources, AT-derived MSCs (AT-MSCs) are easy to obtain [ 43 ], have less genomic instability and senescence than BM-derived MSCs [ 44 ], harbor higher proliferation capacities [ 37 , 45 ], and are superior in inducing anti-inflammatory effects and surviving after transplantation [ 37 , 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental [ 36 , 37 ] and clinical [ 38 41 ] studies have demonstrated their effectiveness in the treatment of GVHD, and their low and no expression of human leukocyte antigens (HLA) class I and class II, respectively, make them ideal targets for allogeneic transplantation [ 42 ]. Compared to other sources, AT-derived MSCs (AT-MSCs) are easy to obtain [ 43 ], have less genomic instability and senescence than BM-derived MSCs [ 44 ], harbor higher proliferation capacities [ 37 , 45 ], and are superior in inducing anti-inflammatory effects and surviving after transplantation [ 37 , 45 , 46 ]. Accordingly, it has recently been shown that these features can empower AT-MSCs to demonstrate better protection against aGVHD (compared to BM- and umbilical cord-derived MSCs) [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation